2011
DOI: 10.1016/j.pec.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic condition self-management: Expectations of responsibility

Abstract: ObjectiveWhile self-management has been shown to be beneficial for many patients it assumes and encourages a particular conception of responsibility and self-management that may not fit with all patients' experience of their chronic conditions and their management. It therefore warrants further examination. MethodsWe examine the concept of self-management and responsibility from a range of standpoints. ResultsAll attempts to meet people's needs run the risk of imposing specific conceptions of how people should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 11 publications
5
73
0
1
Order By: Relevance
“…In line with the above-mentioned culture, one participant directly indicated a preference for medical paternalism, similar to the study of Rogers, Kennedy, Nelson, and Robinson (2005). These findings highlight that matching the need, stage of change and experience with self-management of an individual patient is necessary in order to add value for the individual (Lawn, McMillan, & Pulvirenti, 2011;Lawn & Schoo, 2010).…”
Section: Discussionsupporting
confidence: 69%
“…In line with the above-mentioned culture, one participant directly indicated a preference for medical paternalism, similar to the study of Rogers, Kennedy, Nelson, and Robinson (2005). These findings highlight that matching the need, stage of change and experience with self-management of an individual patient is necessary in order to add value for the individual (Lawn, McMillan, & Pulvirenti, 2011;Lawn & Schoo, 2010).…”
Section: Discussionsupporting
confidence: 69%
“…They reported seeking information from a variety of sources, mainly specialist medical texts (if the participant had access to them), health support organizations, and specialist sites on the internet. Patients such as these meet the criteria for the concordance effect that is the desired outcome of health literacy initiatives [8, 15–17], displaying characteristics of the informed activated patient exemplar of the Chronic Care Model [7]. One study examining the health attitudes, cognitions, and behaviours of individuals seeking health information found that health-oriented individuals utilized active communication channels , which required participant involvement in the critical analysis of health information [3].…”
Section: Resultsmentioning
confidence: 99%
“…Facilitating patient empowerment so that they can be involved in decision-making about their treatment and management involves situating the patient at the centre of their care. 49 The literature argues that in practice, enabling patient empowerment requires placing the patient as professionals in their own right and experts of their own care, bodies, symptoms and situations. 50 This echoes with the finding in this study, in that those practitioners that conceived osteopathy as empowerment sought to generate meaningful, patient-specific cues, pertaining to the impact that patients' pain and dysfunction has on their daily lives and activities.…”
Section: Discussionmentioning
confidence: 99%